If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + 3 = 6a + -8 Reorder the terms: 3 + 9a = 6a + -8 Reorder the terms: 3 + 9a = -8 + 6a Solving 3 + 9a = -8 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 3 + 9a + -6a = -8 + 6a + -6a Combine like terms: 9a + -6a = 3a 3 + 3a = -8 + 6a + -6a Combine like terms: 6a + -6a = 0 3 + 3a = -8 + 0 3 + 3a = -8 Add '-3' to each side of the equation. 3 + -3 + 3a = -8 + -3 Combine like terms: 3 + -3 = 0 0 + 3a = -8 + -3 3a = -8 + -3 Combine like terms: -8 + -3 = -11 3a = -11 Divide each side by '3'. a = -3.666666667 Simplifying a = -3.666666667
| 5(a+3)=25 | | z^2+4z+4= | | (3u-4)(8-u)=0 | | 2x+7y=43 | | 4x^2-8x+4=26 | | 4x^2+4x+1=36 | | 6a+13=55 | | 2x^2+10=-3 | | x^2-18x+81=16 | | 3x^2+1=76 | | (5m+1)=0 | | 6+5a=7a-18 | | (n^2-2)=0 | | (n^2)=0 | | (5m+1)(n^2-2)=0 | | 2x^2-4x+8= | | -9t+8=t | | 5mn^2-10m+n^2-2=0 | | 16(2x-1)=4(x+3)+2x | | (4+u)(3u-7)=0 | | 3y=8*6 | | -16t^2+35t=35 | | -16t^2+35t=30 | | -16t^2+35t=20 | | -16t^2+35t=16 | | 16t^2+x=784 | | x=1+4y | | 17y+13x=19 | | 17x+13y=19 | | x-1=4y | | 4z^2+12z-72= | | (4m+3)(m-7)= |